Rail freight accessibility of the Visegrád Group countries and Baltic States in the context of Eurasian rail transport system - Wilczewska, Martyna (Transport, 2024)
This study aimed to determine the level of infrastructure-based rail freight accessibility and rail freight performance of several Central and Eastern European (CEE) countries in the context of their presence in the Eurasian rail freight transport system. The study′s object was 7 CEE countries: Estonia, Lithuania, Latvia, Poland, Czechia, Slovakia and Hungary. The research methodology was based on the TOPSIS method supplemented with literature and statistical analyses. Several selected numerical indicators were considered to create 2 rankings that displayed the results achieved by countries in terms of accessibility and performance. Results showed that Czechia is the leader in infrastructure-based accessibility, with Latvia closing the ranking, and Lithuania is the leader in rail freight performance, with Hungary closing the ranking. Even though the study did not allow to confirm that a country′s rail freight accessibility affects its rail freight performance and vice versa, it can be assumed that both parameters are crucial in the context of the incoming modal shift to rail freight in Eurasia; therefore, they constitute a valuable research endeavour.